Interference Management in WLAN Mesh Networks Using Free-Space Optical Links - Rajakumar, V.; Smadi, M.N.; Ghosh, S.C.; Todd, T.D.; Hranilovic, S. (Journal of lightwave technology, 2008)
Frequency channels are assigned in wireless local-area network (WLAN) mesh networks subject to strict cochannel interference constraints. Since Wi-Fi may be freely used by other networks, added interference may eventually invalidate the original frequency assignment, making full link activation impossible. In this paper, we address this problem by selectively installing supplementary free-space optical (FSO) links when radio-frequency (RF) link performance has deteriorated. To minimize cost, the number of FSO links that are needed should be as small as possible. We first formulate the channel assignment problem with the objective of maximizing the number of simultaneous link activations while satisfying cumulative RF interference constraints. A proof is given for the NP-completeness of the joint frequency assignment and FSO link placement problem. We then propose an efficient heuristic to solve the channel assignment problem using a genetic algorithm. Results are then presented for various mesh networks which show that the proposed algorithm has good results compared with the computed bounds. The presented results show that the use of FSO links permits WLAN mesh network deployment in interference-prone situations.